TINJAUAN YURIDIS PENETAPAN PERUBAHAN NAMA DI PENGADILAN AGAMA KEBUMEN - Eldi Harponi; Francisca Romana Harjiyatni; Sunarya Raharja (Kajian Hasil Penelitian Hukum, 2018)
Research titled JURIDICAL REVIEW THE CHANGE OF NAME IN RELIGIOUS COURT KEBUMEN, aims to understand judicial consideration religious court judge kebumen case in order to change of name on the marriage, do things change the name was a marriage book including the authority absolute the religious court kebumen to examine and terminating, according to the rules set in article 49 Undang-Undang Number 7 Years 1989 about religious court of covering marriage, die and leave wives behind, last will and testament, and grants no wreceived loans, for religious or community  use, zakat, infaq, shadaqah and economic field sharia.This research is normative research, in addition, also conducted field research, which is directli related to the object under study. The aim of study is to understand the legal sense of the court of the Religious Court in Kebumen, in the name replacement decision case.Consideration court judge religion kebumen is that matter changes to the program name in a marriage book is competence absolute the religious court kebumen, with a consideration that changes to the program name in a marriage book still related in the matrimonial law and in accordance with the principle of personalitas subjects attached to the religious court, and also about prohibition for court to refuse check, judge and cut a matter filed with a pretext that law no or less definitely, but obliged to examine and prosecute, and there is an obligation to judge to dig, following and understood the need and values law the living and developing in community which called the living law.Keywords: Determination, Name Change, Religious Court